Differences in kicking dynamics of futsal and soccer ball - Peacock, J.; Garofolini, A.; Oppici, L.; Serpiello, F.; Ball, K. (ISBS Proceedings Archive (Michigan), 2017)
Differences in equipment influence the execution of a skill. To date, no literature has identified if ball properties influence foot-ball impact of kicking. The aim of this study was to compare kick impact characteristics of a futsal (FB) and soccer ball (SB). A mechanical limb impacted each ball to standardise all kicking characteristics. High speed video camera (4,000 Hz) captured impact characteristics of each ball. Significant differences (P < 0.05) were observed between the two balls. The SB displayed a higher coefficient of restitution, average force and ball velocity. The timing of key events during impact differed; the FB velocity was higher for the first 75% of impact duration, where it was then exceeded by the SB. The SB was characterised by decreased energy losses, notable during the reformation phase. This work identified that ball properties do influence the impact phase of kicking.